(untitled) (Dhaka University Journal of Applied Science and Engineering, 2022)
The increasing use of radiation especially low radiation in everyday life demands an evaluation of the performance of dosimeter in the respective environment. The present work is concerned with the investigation of the thermoluminescence (TL) response of TLD-100 in a low radiation dose environment. Ten Harshaw TLD-100s were collected from Health Physics Division, Atomic Energy Centre, Dhaka, Bangladesh and irradiated at different low dose radiation such as 46.82μGy, 93.82μGy, 140.73μGy, 187.54μGy and 234.1μGy with 90Sr/90Y Irradiator and readout by Harshaw 4500 TLD Manual Reader. Following the reading, detection limit, linearity, variation of standard deviation, and coefficient of variation were investigated. After that, the same TLDs were irradiated at a dose of 140.46μGy and fading test was incorporated for 7 days. TLD-100 upon low dose irradiation showed a good linear response (Coefficient of Determination, R2 ̴1) as well as a lower detection limit (DL). The value of DL has been found 40μGy. Standard deviation and coefficient of variation form a decreasing pattern with increasing low radiation. For a very short time period like 7 days, TLDs showed an irregular response. These investigations help conclude that TLD-100 can be used for low dose environments with proper calibration and correction factor calculation. DUJASE Vol. 6 (2) 59-63, 2021 (July)